2021
DOI: 10.3389/fmars.2021.732720
|View full text |Cite|
|
Sign up to set email alerts
|

Mercury Accumulation in Marine Sediments – A Comparison of an Upwelling Area and Two Large River Mouths

Abstract: Understanding marine mercury (Hg) biogeochemistry is crucial, as the consumption of Hg-enriched ocean fish is the most important pathway of Hg uptake in humans. Although ocean sediments are seen as the ultimate Hg sink, marine sediment studies on Hg accumulation are still rare. In this context, studying Hg behavior in the marine environment, especially in upwelling environments, is of particular interest due to its importance in these great upwelling regions for the global fishery. There are contradictory stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…However, subduction is typically more signi cant in offshore, oligotrophic regions than in upwelling zones. 32 Therefore, our estimated Hg sinking ux remains valid and has strong positive relationship with upwelling.Similar observations of high Hg sedimentation related to sorption and scavenging was found in the other regions with upwellings (e.g., Antarctic, Peruvian upwelling) [17][18][19] .…”
Section: Cce Upwelling Increases Hg Sinking Ux and Evasionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, subduction is typically more signi cant in offshore, oligotrophic regions than in upwelling zones. 32 Therefore, our estimated Hg sinking ux remains valid and has strong positive relationship with upwelling.Similar observations of high Hg sedimentation related to sorption and scavenging was found in the other regions with upwellings (e.g., Antarctic, Peruvian upwelling) [17][18][19] .…”
Section: Cce Upwelling Increases Hg Sinking Ux and Evasionsupporting
confidence: 79%
“…While studies have highlighted the signi cant input of Hg species to mixed layer due to upwelling, 5,15,16 Zaferani et al (2021) observed high Hg export to sediment in the Peruvian upwelling region, 17 suggesting substantial particle scavenging associated with upwelling. In addition, they noted elevated Hg accumulation rates in the Southern Ocean where high primary production occurs 18 , highlighting the link between Hg cycling and primary production.…”
Section: Introductionmentioning
confidence: 99%
“…13 One explanation is that increased scavenging and remineralization results in increased rates of Hg accumulation within sediment cores, which is correlated with marine productivity. 56 Within these systems, the high THg concentrations remain along the coast, and due to the elevated productivity in the region, upwelling systems are a prime location for Hg incorporation into food webs.…”
Section: Distinct Water Mass Thg Concentrations Due To Scavenging In ...mentioning
confidence: 99%
“…Redeposition of Hg 0 mainly as Hg ++ (because Hg 0 is oxidised in the atmosphere) takes place on terrestrial surfaces by dry deposition, including foliar uptake, sorption, and gas dissolution (Enrico et al, 2016). The ultimate deposition of Hg, probably as HgS ore, is believed to be in ocean sediments (Sanei et al, 2021;Zaferani and Biester, 2021), where part of the inorganic Hg emitted becomes oxidised to Hg ++ and then methylated or in other ways transformed into organomercurials (WHO, 2000;Ignatavičius et al, 2022).…”
Section: Environmental Circulation and Impacts Of Climate Changementioning
confidence: 99%